DRAMA : CLASSICAL VERSUS MODERN - Ade Aini Nuran (BAHAS, 2015)
This study is aimed at explaining classical drama and modern drama in general. It is also purposed to compare the differences between classical drama and modern drama. One of the most significant contrasts between classical drama and modern is the difference in the protagonists. Classical tragedy, for instance, involves royalty, the elite. The idea was that for a character to have a great and far-reaching influence over society he/she had to be in a position of great power and authority. In contrast, modern drama often uses common people as protagonists. Modern drama no longer had its heroes, heroines and villains of days gone by—the subjects of the stories were now ordinary people one might meet any day on the street. Keywords: Drama, Classical, Modern